Antibiotic resistance and consumption before and during the COVID-19 pandemic in Valle del Cauca, Colombia - Isabel Cristina Hurtado; Sandra Valencia; Elisa Maria Pinzon; Maria Cristina Lesmes; Mauro Sanchez; Jaime Rodriguez; Brindis Ochoa; Hemant Deepak Shewade; Jeffrey K. Edwards; Katrina Hann; Mohammed Khogali (Pan American Health Organization, 2023)
Objective. To assess changes in antibiotic resistance of eight of the World Health Organization priority bug-drug combinations and consumption of six antibiotics (ceftriaxone, cefepime, piperacillin/tazobactam, meropenem, ciprofloxacin, vancomycin) before (March 2018 to July 2019) and during (March 2020 to July 2021) the COVID-19 pandemic in 31 hospitals in Valle del Cauca, Colombia. Methods. This was a before/after study using routinely collected data. For antibiotic consumption, daily defined doses (DDD) per 100 bed-days were compared. Results. There were 23 405 priority bacterial isolates with data on antibiotic resistance. The total number of isolates increased from 9 774 to 13 631 in the periods before and during the pandemic, respectively. While resistance significantly decreased for four selected bug-drug combinations (Klebsiella pneumoniae, extended spectrum beta lactamase [ESBL]-producing, 32% to 24%; K. pneumoniae, carbapenem-resistant, 4% to 2%; Pseudomonas aeruginosa, carbapenem-resistant, 12% to 8%; Acinetobacter baumannii, carbapenem-resistant, 23% to 9%), the level of resistance for Enterococcus faecium to vancomycin significantly increased (42% to 57%). There was no change in resistance for the remaining three combinations (Staphylococcus aureus, methicillin-resistant; Escherichia coli, ESBL-producing; E. coli, carbapenem-resistant). Consumption of all antibiotics increased. However, meropenem consumption decreased in intensive care unit settings (8.2 to 7.1 DDD per 100 bed-days). Conclusions. While the consumption of antibiotics increased, a decrease in antibiotic resistance of four bug-drug combinations was observed during the pandemic. This was possibly due to an increase in community-acquired infections. Increasing resistance of E. faecium to vancomycin must be monitored. The findings of this study are essential to inform stewardship programs in hospital settings of Colombia and similar contexts elsewhere.